Comprehensive Valorization of Pineapple Cultivation Residues for High-Value Products: A Global Perspective Review - Vargas-Vargas, Maynor Alberto (2025)
Pineapple cultivation generates significant agro-industrial residues, such as peels, crowns, cores, and stubble, which are often discarded despite their potential as valuable raw materials. This review aims to provide a comprehensive assessment of the sustainable valorization of these residues through emerging bio-based technologies. The objective is to critically examine the scientific evidence on their transformation into high-value products in renewable energy, agriculture, bioplastics, and nutraceuticals. Methodologically, this review analyses peer-reviewed literature recently published, selected from academic databases, with emphasis on studies from tropical regions in Asia, Latina America, and Africa. Selection criteria included technological feasibility, environmental relevance, and consistency with circular bioeconomy principles. Results show that pineapple residues, rich in lignocellulosic fibers, sugars, and bioactive compounds, can be converted into bioethanol, biogas, hydrogen, bioplastics, natural dyes, and dietary supplements. In agriculture, biochar and organic fertilizers derived from compost enhance soil health, increase crop productivity, and reduce chemical inputs. Pineapple by-products are also valuable for producing biodegradable packaging, textiles, and natural dyes, offering sustainable alternatives to fossil-based materials. Bioactive compounds such as bromelain and antioxidants extracted from pineapple residues have applications in functional foods, pharmaceuticals, and cosmetics. Natural fibers from crowns and peels are utilized in bioplastics and composite materials, advancing circular economy principles and reducing environmental impacts. Despite their potential, challenges such as technology scalability and market integration remain. By transforming agricultural waste into high-value products, the pineapple industry can contribute to economic growth, environmental preservation, and the development of sustainable industries aligned with circular economy goals.